MENTAL HEALTH AND WELL-BEING IN CHILDREN: THE PROTECTIVE ROLE OF RESILIENCE, SELF-ESTEEM, SELF-EFFICACY, AND PARENT-CHILD RELATIONSHIP - Ioannidou, Louiza; Michael, Katerina (Psychological thought, 2024)
Stressful and adverse events pose a challenge to children’s mental health and well-being, as they are associated with internalizing and externalizing problems. The present study examined how family and individual factors act protectively to enhance children’s mental health and well-being. The study involved 421 children aged 9 to 12 and their parents/guardians. Children and parents completed questionnaires concerning their mental resilience, children’s self-esteem and self-efficacy, children’s mental difficulties, and child-parent relationships. Research findings indicated that children with high self-esteem and self-efficacy display more significant levels of mental resilience.  Furthermore, children develop fewer mental difficulties when parents and children have high resilience and engage in positive interaction practices. The study also highlighted that children's self-esteem predicts resilience through the mediating role of children's self-efficacy. Additionally, parents' resilience indirectly impacts children's mental health through children's resilience and parent-child closeness relationships. The findings underscore the importance of developing prevention programs to bolster children's resilience and well-being.